2022
DOI: 10.1007/s10567-022-00384-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Community Mental Health Programs for Australian Youth: A Systematic Review

Abstract: Australia has undergone significant youth mental health reform over the past 10 years, leading to numerous studies examining the effects of community-based mental health care programs for Australian youth. However, no synthesis of this literature currently exists. Therefore, this systematic review aimed to: (1) describe the types of community-based mental health programs that have been delivered to Australian youth in the past 10 years; and (2) examine their impact in improving young people’s mental health sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 89 publications
(274 reference statements)
0
10
0
Order By: Relevance
“…This was also con rmed in recent service mapping of mental health services across the state. 32 Young people and carers acknowledged that existing services are only addressing the 'tip of the iceberg', and consistently called for greater holistic support, including schooling, work, activities of daily living, engaging in community/hobbies/activities, housing, and healthy lifestyle behaviours. This is particularly relevant for young people in the 'missing middle' who felt that current services did not meet their clinical or psychosocial needs.…”
Section: Discussionmentioning
confidence: 99%
“…This was also con rmed in recent service mapping of mental health services across the state. 32 Young people and carers acknowledged that existing services are only addressing the 'tip of the iceberg', and consistently called for greater holistic support, including schooling, work, activities of daily living, engaging in community/hobbies/activities, housing, and healthy lifestyle behaviours. This is particularly relevant for young people in the 'missing middle' who felt that current services did not meet their clinical or psychosocial needs.…”
Section: Discussionmentioning
confidence: 99%
“…These include New Zealand’s Youth One Stop Shops [ 27 ], Youth Wellness Hubs in Canada [ 28 ], and Jigsaw in Ireland [ 29 ], which provide clinical mental health support and social care services embedded in a single community-based setting delivered by a multidisciplinary team, aiming to ameliorate care fragmentation, service navigation and accessibility barriers for youth. However, there is a lack of such models that have been implemented and evaluated within Australia [ 30 ]; Orygen Youth Health in Victoria recently launched psychosocial support packages for young people aged 16–24 years experiencing moderate to severe mental illness [ 31 ]. It is clear that greater integration within the Tasmanian youth mental health sector is required so that young people have access to both clinical and social care support to enhance their psychosocial wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were aged between 1 and 9 years to address the lack of synthesis focused on young children (i.e. prior to adolescence), as a recent Australian review has previously examined mental health programmes for young people aged 10 years and over (Savaglio et al, 2022). This age range encompasses national and international definitions of early childhood (Department of Health and Human Services, 2020), and includes the years prior to the onset of adolescence (UNICEF, 2022).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…However, there is limited synthesis of research conducted in the Australian context. While a recent Australian review found that community-based mental health programmes for adolescents and young people aged 10–25 years experiencing mental illness can alleviate internalising symptomatology (Savaglio et al, 2022), the overall impact of targeted programmes for younger Australian children specifically, remains unclear. Furthermore, the majority of the existing local and international literature focuses on universal mental health programmes, particularly in the school setting (e.g.…”
mentioning
confidence: 99%